In vitro propagation of Sabah's endangered jewel orchid, Macodes limii - Halyena Indan (2018)
Macodes limii is a terrestrial jewel orchid of Sabah that grows in the deep shade and moist forest floor. It is highly valued for its unique leaves with sparkling golden yellow veins on blackish to purplish background of leaves. However, this species is recognised as an endangered species by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) due to over-collection and the loss of its suitable habitats. Through in vitro propagation of orchids, the problems can be overcome and protect this orchid from extinction by maintaining them in tissue culture or acclimatised as ex situ germplasm. In this study, protocols for in vitro propagation of Macodes limii using seeds and vegetative explants (shoot tip and nodal explants) were developed. The study on flowers, capsules and seeds biology (development and morphology), photoperiods (24-hour light, 16-hour light, 24-hour dark), complex additives (peptone, coconut water, banana homogenate) and plant growth hormones (BAP, Kin, TDZ, NAA, IAA, IBA) on asymbiotic seed germination, protocorm development and in vitro axillary shoot formation of Macodes limii were investigated. Immature capsules from artificial hand-pollinated of two to three-day aged flowers were harvested between days 21 to 23 for asymbiotic seeds germination. Seeds incubated under 24-hour dark produced the best germination response (29.6±3.57%) followed by 16-hour light (1.7±0.50%). No seeds were germinated under 24-hour light and thus, the beneficial effect of continuous darkness in asymbiotic seeds germination of Macodes limii was used for subsequent study. Higher seed germination percentage was observed on ½ strength MS medium with addition of 5% (w/v) banana homogenate (14.5±3.50%). The presence of 0.5 mg/L BAP in the medium also enhanced seed germination by 8.5±3.77%. Protocorms from seeds germinated under 24-hour dark condition were successfully regenerated and developed under the presence of light (16-hour light). Decontamination of apical shoot tip explant from ex vitro resulted in lower percentage of contamination (20±0.45%) and higher percentage of survival (60±0.55%) when immersed in 2% (v/v) CloroxTM for 15 minutes, as compared to nodal explant. The highest number of axillary shoots (four shoots per explant) and the longest axillary shoot (4.67±0.54 cm) were obtained on 0.5 mg/L TDZ using shoot tip explants. The well-developed shoots were further cultured on 1.0 mg/L IAA to initiate two to three roots with the length of 2.12±0.41 cm. The rooted plantlets were successfully acclimatised in a greenhouse after three months. The data presented in this study delivered new information for a better understanding of the propagation and conservation of this Sabah’s orchid.